Geração de uma vacina recombinante experimental contra o vírus da imunodeficiência felina subtipo B (FIV-B) baseada no vetor viral vaccinia ankara modificado (MVA)) - Luis Adan Flores Andrade (2016)
The feline immunodeficiency virus (FIV) is a retrovirus with global impact, affecting both domestic and wild cats. This virus can cause a severe and progressive immunosuppression culminating in the death of the cat. Since the discovery of FIV, only one vaccine has been commercialized. This vaccine has its efficiency proven against FIV subtype A and subtype D, whereas subtype B (FIV-B) which is the subtype circulating in Brazil, has not a vaccine available. The basis of any program of prevention is vaccination to achieve an effective and lasting immunity. So an effective vaccine against FIV subtype B is required to combat this virus. The objective of this study was to develop and evaluate a vaccine against FIV-B using the Vaccinia Ankara Modified (MVA) recombinant vírus as a vaccine vector expressing the variable region V1-V3 of the FIV-B envelope. Among the advantages of this technology over traditional vaccines already tested against FIV, we can highlight: the production of high levels of recombinant antigen within the cell, a potential adjuvant effect, and the ability to induce both cellular and humoral response in the host. In this work, we evaluated the immunogenicity of the vaccine in mice. For this purpose, mice C57BL/6 were immunized and after 21 days they received a booster dose. We demonstrated the generation of antibodies against the FIV subtype B envelope protein, which do not cross recognize the envelope protein of FIV subtype A, demonstrating that this vaccine generates a specific response against subtype B. In addition, it was observed that the sera from cats naturally infected with FIV were also able to recognize the envelope protein of FIV, produced by the vaccine virus. We also evaluated the cellular immune response against epitopes present in V1-V3 region of the FIV envelope gene. Our results suggested that a good cellular response was induced, as measured by splenocyrtes proliferation and IFN-y production in a murine immunization model. The data obtained in this study lead us to believe that this vaccine is a promising candidate to be evaluated in cats. This product has the potential to be bsorbed into a market in expansión, the so called PET market.